DEVELOPEMET OF COLO SPECIFIC DRUG DELIVERY OF ACECLOFEAC BY USIG EFFECTIVE BIDER SYSTEM OF ETHYL CELLULOSE - RAOSAHEB S. SHENDGE; FATIMA J. SAYYAD; KISHOR S. SALUNKHE; RASIKA D. BHALKE (International Journal of Pharma and Bio Sciences, 2010)
Colon targeted drug delivery system by using dextrin, polysaccharide, as a carrier for Aceclofenac is the objective of the present study. Very common wet granulation technique is used for preparation of matrix tablet. Different binder like ethyl cellulose, sodium CMC and sucrose were used during preparation of matrix tablets containing dextrin and various excipients. Evaluation was done by different IPQC tests, content uniformity and in vitro drug release study. Drug release profile was evaluated in simulated gastric, intestinal fluid and simulated colonic fluid. Drug release profile in simulated gastric, intestinal fluid and colonic fluid decide the best formulation. The matrix tablet containing binder system of ethyl cellulose and dextrin as a carrier was found to be suitable for targeting the colon as compare to other matrix tablets containing different binders because of fewer amounts (8-10%) of drug release in the simulated gastric and intestinal fluid. Matrix tablets containing dextrin releases 82.43 % of Aceclofenac in simulated colonic fluid with 4 % human fecal matter solution. No change was found in physical appearance and dissolution profile upon storage at 400C / 75 % relative humidity for six months with the tablets containing dextrin polysaccharide as a carrier. Ethyl cellulose as binder was most suitable binder to deliver the drug specifically in colonic region as compare to matrix tablets of dextrin with other binder systems.